Penetrative osseointegrative phospholipid coatings on 3D titanium lattice structures - Hudson, Hannah Katherine, author; James, Susan, advisor; Prawel, David, committee member; Ehrhart, Nicole, committee member (Colorado State University. Libraries, 2012)
Titanium is a commonly used material for implantable metallic devices though these devices still have many issues. The cost of implant surgery and the likely revision surgery that will follow is high. Cementless implants frequently fail due to aseptic loosening of the device, typically as a result of poor osseointegration. Phospholipids are naturally occurring substances that have been used to enhance new bone growth and integration of this bone with the implants. Electrospraying (e-spraying) is a method that uses electrical forces to drive source material to a target conductor. It typically has very high efficiency because it uses electrical charge to carry the material. This process also provides good control of coating morphology as this can be effected by the parameters used to e-spray. In our work the E-spraying technique was used to apply coatings of 1,2-dioleoyl-sn-glycero-3-phospho-L-serine (DOPS) to Ti-6V-4Al porous lattice structures. These lattice structures are created using Electron Beam Melting (EBM). This manufacturing process is an additive process, part of the solid free form fabrication group, a subset of rapid prototyping. EBM enables precise control of complex geometries. When e-spraying these lattice structures can become Faraday cages when an electric field is applied to them. A Faraday cage is a conductor that becomes an equipotential surface when an electric field is applied and thus in its interior lacks an electric field. The exclusion of an internal electric field can inhibit to the e-spray process which relies on field lines to carry material to the target. In our work the Faraday cage effect was observed in two conditions, one in which the lattice structures were externally, circumferentially insulated and one in which the lattices were not insulated. Three different porosity lattices, with different pore sizes, were tested and all became Faraday cages when insulated and only the lowest porosity lattice became a strong Faraday cage when not insulated. The lattices that did coat did not exhibit conformal and uniform coatings when the Faraday cage effect was present. E-spray parameter variation was not able to mitigate the Faraday cage effect nor was it able to affect the morphology of the coatings. The surface topography of the structures is important for preferential cell adhesion and can be controlled using acid etching to modify the surface. In attempt to coat titanium lattice structures with a phospholipid coating this work discovered the Faraday cage effect as it relates to the electrospraying of phospholipids. It currently defines the limitations of the e-spray process as well as outlines what has been tried to mitigate the Faraday cage effect and discover how the Faraday cage effect changes coating morphology. In the future continuing work on mitigating the Faraday cage effect will be done as well as combining the e-spray process with one that uses a mechanical force to accelerate particles.